AN ANALYSIS OF STUDENTS WRITING SKILL IN PARAGRAPH WRITING - Abdul Rohim (Universitas Muhammadiyah Tangerang, 2019)
Paragraph writing can be very simple and complicated in the same time, because writing takes time and needs skills. Dealing with that statement a descriptive research is conducted in Muhammadiyah University of Tangerang. The objective of this research is to analyze students’ skill in their paragraph writing. After analyzing the data quantitatively and qualitatively, it is found that the students’ skill in their paragraph writing is 15,13Key words: Writing, Paragraph writing